Performance of Saniri in Village Government System in Central Maluku Regency - Pieter S Soselisa; Ivonny Y Rahanra; Rugayah Alhamid (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2023)
Saniri is part of the state government which has the duties, functions, and authorities which are listed and stipulated in the Regional Regulation of Central Maluku Regency Number 04 of 2006. Saniri is formed to support the administration of state government, nd and is domiciled as a supporting element for the administration of the state government and partners of the head of state government. Thus, in the state government, Saniri has a big role and occupies an important position, because it can determine the direction of development to be achieved by the community through the State Government. As part of the state government as well as the representation of the people of the country, the state Saniri must be able to synergize with the state government in carrying out its duties and responsibilities. Saniri must understand their duties, authorities, and responsibilities, with good performance. Because performance is success in carrying out tasks or work results that can be achieved by a person or group in an organization in accordance with their respective authorities and responsibilities or about how a person is expected to function and behave in accordance with the tasks assigned to him and the quantity, quality and time spent on the task. Indeed, achieving good performance is strongly influenced by various factors, both internal and external factors. This study uses a qualitative method that aims to examine and analyze the factors that influence the performance of the saniri in carrying out their duties, functions, and responsibilities in the country's government.